FROM DISCIPLINE TO EXCELLENCE: ANALYZING THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATOR - Fajar, Bintang Nur Kurnia; Setiani, Setiani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Purpose of the study is to understand the role of mediation organizational commitment to influence work discipline as an enhancer of performance employees. Study This done in Body Staffing And Development Source Power Man Regency Poor. The population overall on research is 71 employees, with a sample of 71 employees. Study This uses a type Non-Probability Sampling technique taking the saturated sample. The process takes data with a deployment questionnaire. Type study Which used in study This use method quantitative. Analysis data used in the study This is used approach explanatory research . Study This uses SmartPLS 4.0 software . Data collection instruments through questionnaires, interviews and observations. Measured questionnaire with scale Likert. Results show that work discipline is influential in a manner positive And significant to performance employees and organizational commitment employees. Then quality organizational commitment employees also influence in a manner positive and significant to performance employee. So Also, organizational commitment proven to a manner positive And significant can become mediation in influencing work discipline to performance employee.